2017 IEEE Automatic Speech Recognition and Understanding Workshop (ASRU) 2017
DOI: 10.1109/asru.2017.8268979
|View full text |Cite
|
Sign up to set email alerts
|

Topic segmentation in ASR transcripts using bidirectional RNNS for change detection

Abstract: Topic segmentation methods are mostly based on the idea of lexical cohesion, in which lexical distributions are analysed across the document and segment boundaries are marked in areas of low cohesion. We propose a novel approach for topic segmentation in speech recognition transcripts by measuring lexical cohesion using bidirectional Recurrent Neural Networks (RNN). The bidirectional RNNs capture context in the past and the following set of words. The past and following contexts are compared to perform topic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…More recently, Sehikh et al (2017) utilized long short-term memory (LSTM) networks and showed that cohesion between bidirectional layers can be leveraged to predict topic changes. In contrast to our method, the authors focused on segmenting speech recognition transcripts on word level without explicit topic labels.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, Sehikh et al (2017) utilized long short-term memory (LSTM) networks and showed that cohesion between bidirectional layers can be leveraged to predict topic changes. In contrast to our method, the authors focused on segmenting speech recognition transcripts on word level without explicit topic labels.…”
Section: Related Workmentioning
confidence: 99%
“…These context-dependent models assume that utterances with a similar semantic distribution share the same topic. More recent methods leverage the deep architectures, such as recurrent neural networks (RNNs) (Sehikh et al, 2017) and convolutional neural networks (CNNs) (Wang et al, 2016) to semantically encode the utterance into a vector space. Treating the topic segmentation as a sequence labeling problem, labels (i.e., topics) are then assigned to every utterance.…”
Section: Topic Segmentationmentioning
confidence: 99%
“…Recently, proposed SegBot, a bidirectional RNN coupled with a pointer network that addresses both topic segmentation and EDU. Also, LSTM or CNN based approaches have been proposed, for instance through bidirectional layers (Sheikh et al, 2017), sentence embedding-based with four layers bidirectional LSTM (Koshorek et al, 2018) or through two symmetric CNN (Wang et al, 2017), etc. Finally, Arnold et al (2019) proposed Sector, the first LSTM-based architecture that combines topical (latent semantic content) and structural information (segmentation) as a mutual task.…”
Section: Related Workmentioning
confidence: 99%